Trakea adenoid kistik karsinomu olgusu - (:unkn) unknown (My University, 2000)
Göğüs cerrahlarının yakın zamanlara kadar çekinerek müdahale ettiği trakeanın cerrahi gerektiren patolojileri oldukça düşük bir insidansa sahiptir. Diğer taraftan oluştuklarında, yol açtıkları şiddetli nefes darlığı şikayetleri nedeni ile acil tedavi gerektirirler. Trakeanın en sık primer tümörü olan adenoid kistik karsinom, ilk sırada bulunmamakla birlikte, yine de hava yolu tıkanmasının başta gelen nedenlerindendir. Oldukça uzun bir bölünme hızına sahip olan bu tümörlerde cerrahi ve radyoterapi kombinasyonu yüz güldürücü sonuçlar vermektedir. Bu yazıda da distal trakeada yerleşmiş ve tama yakın havayolu tıkanmasına neden olan bir adenoid kistik karsinom olgusunun cerrahi tedavisi sunulmaktadır.

The trachea is one of the latest organs that thoracic surgeons dealt with and its surgical pathologies present a considerably low incidence. On the other hand, once occurred, they necessitate an urgent treatment in order to relieve the severe airway obstruction that they cause. Although the primary tracheal tumors, especially the adenoid cystic carcinoma, are not the most common cause of airway obstruction, still they are counted as one of the major ones. As adenoid cystic carcinoma of trachea have a very long doubling time, the combination of surgery and radiotherapy gives remarkably good prognostic results. This is a case report of a patient with an adenoid cystic carcinoma in distal trachea, which causes a near total obstruction.
Case report of a tracheal adenoid cystic carcinoma
Keywords: Kalp ve Kalp Damar Sistemi; Cerrahi